2016
DOI: 10.6007/ijarafms/v6-i1/1997
|View full text |Cite
|
Sign up to set email alerts
|

Financing of Innovative Small and Medium-Sized Enterprises. A Research in Turkey

Abstract: Today's business realm involves a vast variety of businesses and business groups; small and medium-sized enterprises (SMEs) being one of the most prominent. Despite countless investigations from many different business-related perspectives, their innovation perspective is rarely subjected. This current study chooses this perspective and moves a step beyond by considering financing of these businesses. In other words, this study covets to uncover how innovative SMEs are financed, how much these businesses care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…Regarding the 'preference for funding sources' variable, the results obtained are consistent with the empirical evidence that concluded that the companies that innovate follow the order of the preferences of the funding sources predicted by pecking order theory (Myers & Majluf, 1984)-that is, once companies develop innovation activities, they make greater use of internal funds, but as the culture of innovation is imposed on the company, external funds are used more (Bartoloni, 2013;Kerr & Nanda, 2015;Ullah et al, 2010). This evidence is also related to the result obtained on the variable 'sources of short-term financing', which suggests that companies prefer to finance their innovation projects with internal funds in the short term (Ayranci & Ayranci, 2016;Serrasqueiro et al, 2016). In the Colombian case, studies such as the one by Sierra et al (2009) suggested that Colombian manufacturing companies-especially large and small companies-finance their innovation projects with internal funds.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Regarding the 'preference for funding sources' variable, the results obtained are consistent with the empirical evidence that concluded that the companies that innovate follow the order of the preferences of the funding sources predicted by pecking order theory (Myers & Majluf, 1984)-that is, once companies develop innovation activities, they make greater use of internal funds, but as the culture of innovation is imposed on the company, external funds are used more (Bartoloni, 2013;Kerr & Nanda, 2015;Ullah et al, 2010). This evidence is also related to the result obtained on the variable 'sources of short-term financing', which suggests that companies prefer to finance their innovation projects with internal funds in the short term (Ayranci & Ayranci, 2016;Serrasqueiro et al, 2016). In the Colombian case, studies such as the one by Sierra et al (2009) suggested that Colombian manufacturing companies-especially large and small companies-finance their innovation projects with internal funds.…”
Section: Discussionmentioning
confidence: 73%
“…Our main interest is to identify the most relevant financial variables in the development of (product and process) innovation activities in SMEs in an emerging country such as Colombia. We found that most studies in the field of innovation financing focus on the topics of capital structure (Bartoloni, 2013;Boyer & Blazy, 2014;Egger & Keuschnigg, 2015), use of (external/internal) sources of financing (Ayranci & Ayranci, 2016;Kerr & Nanda, 2015;Leiponen & Poczter, 2014;Poczter & Leiponen, 2016;Serrasqueiro et al, 2016), the availability of funding sources (Hall et al, 2016;Kaufmann & Tödtling, 2002), and restrictions on obtaining financing for innovation (Brancati, 2015;Canepa & Stoneman, 2008). Additionally, different models and theories such as agency cost theory (Jensen & Meckling, 1976), moral hazard theory (Holmstrom, 1989), the cost of capital (Mossin, 1966;Sharpe, 1964;Treynor, 1961), and different capital structure models (Berger & Udell, 1998;Modigliani & Miller, 1958;Myers & Majluf, 1984) have sought to inform the field of financing innovation.…”
Section: Related Literaturementioning
confidence: 98%
See 1 more Smart Citation